Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00542-009-0989-9
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-assisted low pressure room temperature lamination of low temperature cofirable ceramic green tapes for formation of embedded micro channels

Abstract: Low temperature cofired ceramic substrates are becoming increasingly attractive for high density electric circuits and microsystems. Embedded micro patterns such as channels and cavities in ceramic substrates are indispensable for circuit cooling and media transportation. One of process challenges is how to make these embedded micro channels and cavities, which would be collapsed or deformed under conventional lamination. This paper reports on a novel solvent-assisted lamination that could provide low pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Other chemical lamination methods are very similar to the one described above. The tapes can be temporarily bonded by some adhesives [92][93][94] or laminated using solvents [95][96][97]. Chemical bonding is not as universal as the thermocompressive method.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Other chemical lamination methods are very similar to the one described above. The tapes can be temporarily bonded by some adhesives [92][93][94] or laminated using solvents [95][96][97]. Chemical bonding is not as universal as the thermocompressive method.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…By means of pushing individual droplet of liquid materials through a nozzle on various substrates, electrode arrays are acquired with high efficiency. Inkjet printing presents more precise deposition, which appears superior to screen printing or some traditional deposition techniques such as lamination, [52,53] drop-casting, [54,55] and sputtering. [56,57] With the diversity of wide-range printable solvents, inkjet printing has become an alternative with high promise to conventional MBs' fabrication techniques.…”
Section: Inkjet Printingmentioning
confidence: 99%
“…The process of joining the tape casts is possible because the green tape casts consist of organic materials that show plastic behavior . The pressure and temperature of conventional lamination processes range from 5 to 20 MPa and 70 to 90°C, respectively. The high lamination pressure and elevated temperature impose limitations on the conventional lamination process.…”
Section: Introductionmentioning
confidence: 99%
“…Jurkow et al employed a solvent‐assisted chemical lamination approach called cold chemical lamination to compress the ceramic tapes under a pressure below 0.5 MPa. Shan et al reported a solvent‐assisted lamination method for the lamination of ceramic green tapes at a low pressure and room temperature. Thus, the ceramic green tapes can be joined by solvent‐assisted lamination …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation